THE ROLE OF ONLINE INTERACTION TOOLS IN ENHANCING SPEAKING PROFICIENCY IN ENGLISH LANGUAGE TEACHING (SCIENCE TIME JOURNAL, 2025)
The integration of online interaction tools into English Language Teaching (ELT) has significantly transformed approaches to developing speaking skills. This article provides an in-depth review of synchronous and asynchronous platforms, such as Zoom, Microsoft Teams, Flip and Padlet, examining their impact on learners’ speaking proficiency. Findings suggest that these tools create diverse communicative opportunities that enhance fluency, accuracy, motivation and learner autonomy. While technical and digital literacy challenges exist, they can be mitigated through effective pedagogical strategies and support. This study concludes that online interaction tools are vital for modern ELT, enabling flexible and engaging oral practice that parallels or surpasses traditional classroom experiences. Recommendations for teachers and future research directions are also discussed.